The Abbreviated Overall Anxiety Severity and Impairment Scale (OASIS) and the Abbreviated Overall Depression Severity and Impairment Scale (ODSIS): Psychometric Properties and Evaluation of the Czech Versions - Sandora, Jan; Novak, Lukas; Brnka, Robert; van Dijk, Jitse P; Tavel, Peter; Malinakova, Klara (International journal of environmental research and public health, 2021)
Short and effective tools for measuring depression, anxiety and their resulting impairments are lacking in the Czech language. The abbreviated versions of the Overall Anxiety Severity and Impairment Scale (OASIS) and the Overall Depression Severity and Impairment Scale (ODSIS) show very good psychometric properties in English and other languages, and can be used in different settings for research or clinical purposes. The aim of this study was the psychometric evaluation and validation of the Czech versions of the abbreviated forms of both tools in the general population. A nationally representative sample of 2912 participants (age = 48.88, SD = 15.56; 55% female) was used. The non-parametric testing of the differences between sociodemographic groups revealed a higher level of anxiety and depression in students, females and religious respondents. Confirmatory Factor Analysis suggested a good fit for the unidimensional model of the OASIS: x2(4) = 38.28; p < 0.001; TLI = 0.999; CFI = 0.997; RMSEA = 0.078; SRMR = 0.027 and the ODSIS: x2(4) = 36.54; p < 0.001; TLI = 0.999; CFI = 0.999; RMSEA = 0.076; SRMR = 0.021 with the data. Both scales had an excellent internal consistency (OASIS: Cronbach's alpha = 0.95, McDonald's omega = 0.95 and ODSIS: Cronbach's alpha = 0.95, McDonald's omega = 0.95). A clinical cut-off of 15 was identified for the OASIS and a cut-off of 12 for the ODSIS. The study showed good validity for both scales. The Czech versions of the abbreviated OASIS and ODSIS were short and valid instruments for measuring anxiety and depression.
Keywords: Surveys and Questionnaires; Humans; lidé středního věku; úzkost; jazyk (prostředek komunikace); Female; faktorová analýza statistická; anxiety; lidé; Anxiety; Factor Analysis, Statistical; reprodukovatelnost výsledků; průzkumy a dotazníky; Language; COVID-19; ženské pohlaví; Male; Reproducibility of Results; Middle Aged; Czech versions; psychometric properties; Psychometrics; Czech Republic; Depression; ODSIS; Česká republika; mužské pohlaví; deprese; psychometrie; depression; OASIS